The Discourse of Tionghoa Muslim Identity in Indonesia After the Reform Order: A Critical Discourse Analysis of ‘Komunitas’ - ‘Cheng Hoo’ Magazine - Ahmad Alwajih (Department of Communications, Universitas Islam Indonesia, 2020)
The discourse of Indonesian Chinese Muslim identity has been shaped through long historical processes. Since the colonialism era to the Reform Order, this discourse has changed due to the economic and political transformation, which in turn give an impact to the structure of the identity itself. The Reform Era is one of social ruptures in Indonesia that become interesting historical context to examine how the discourse of Indonesian Chinese Muslim has been developed. This study has examined the notions of identity through a critical discourse analysis model as proposed by Norman Fairclough, which emphasizes both sociocultural practice of discourse and micro level of discourse. Taking Komunitas - Cheng Hoo magazine as a case study, this study aims to outline the discourse on Chinese Muslim identity in Indonesia in the post-New Order context. As one of the results of political reform in Indonesia which has opened up the opportunity for the Chinese communities to express their identity, this magazine emphasizes various positive representations of Chinese communities and their cultures. However, such positive representations also entail dynamic tensions of Chinese identities, i.e., tension between ‘Chinese’ and ‘Tionghoa’ terms, between nationalism and discrimination issues, and tension of being apolitical or political subject. This study also finds that the representation of Chinese Muslim is not singular, but plural, fluid and constantly in contestation with the others. Most importantly, Chinese Muslims are represented as inclusive-rational groups and as true nationalist people. Keywords: critical discourse analysis, Indonesian Chinese Muslim, identity, Reform Order.